Banana Milk Delicieuse Enterprise / Nadia Nabela Abdullah ... [et al.] - Abdullah, Nadia Nabela; Mustapha, Siti Musliha; Md. Khairul Khadi, Nurain; Rosseli, Nurul Hayani; Abdul Rahman, Natasha Amirah (2021)
This business is based on partnership, where it consists of five members who hold important positions in the company such as General Manager, Administrative Manager, Marketing Manager, Operational Manager, and Financial Manager. Capital of our business is 150,000 thousands. Banana Milk Delicieuse is the only product we sell at our company Banana Milk Delicieuse Enterprise. Our company is located at Seksyen 3, 10, Jalan Bandar Puteri Jaya 3/2, Bandar Puteri Jaya, 08000 Sungai Petani, Kedah. Banana Milk Delicieuse Enterprise is a company that focus on a nutritious and fresh drink made from banana fruits. Banana is one of Malaysia local fruit and suitable to be eaten while dieting. Banana has its own nutrients and has a delicious taste. Thus, that’s why we produced banana milk with a tasty flavor, rich in nutrients, have no added sugar and also can give people instant energy when they drink it. In addition, our business target market is 50% female and 50% male as this product can be enjoyed equally for both gender and it has no gender specification, and also we target peoples which is aged around 14 to 55 years old as our product is healthy and can be consumed for every level of ages. Our product advantages is it is sold with affordable price and the naturally sweet bananas give the milk a delicious and sweet taste. Meanwhile, it have health advantages. The simple steps and ingredients also give many advantages to us and we are very sure that our product can be easily developed and spread in the market without any obstacles. With capital that come from us, we hoping that our company Banana Milk Delicieuse Enterprise is able to achieve great demands from customers. We are very happy if we make our company a well- known established and satisfy the customers with our product quality. This also will be achieved by the full cooperation and efforts among the partners.